B2B Marketing Communication Strategies In Increasing Sales: A Systematic Literature Review - Rudi, Jupensius; Mubarok, Dimas Hamdan; Ar-Rasyi, Hasna Hamida Alifia; Rahayu, Wening Patmi; Dewi, Titis Shinta (IJBLE Scientific Publications Community Inc., 2024)
This research is a Systematic Literature Review (SLR) that adopts PRISMA (Preferred Items for Systematic Review and Meta-Analysis) to investigate business-to-business (B2B) marketing communication strategies in increasing sales. Data were obtained from Scopus, Emerald, Wiley, Taylor and Francis. A total of 96 journals were initially identified, but through the application of strict inclusion and exclusion criteria, the number was reduced to 10 journals that served as the focus of the comprehensive review. The results show that B2B marketing through social media is becoming an integral and connected part of organisations, as it not only helps during the sales process but also during the buying process. Social media has the potential to assist B2B organisations in improving their communication capabilities by facilitating knowledge promotion and encouraging engagement through advanced technology.